Tuning Rigid Polyurethane Foam with Eco-friendly Cellulose Nanocrystals from Oil Palm Empty Fruit Bunches as Energy-Efficient Material Composites for Buildings - Dayanti, Dilla; Christwardana, Marcelinus; Fitria, Nurlaili; Purwoko; Sriariyanun, Malinee; Hidayat; Ridwan, Yohanes Susanto; Sambas; Ilyas, Rushdan Ahmad; Annamalai, Pratheep Kumar; Septevani, Athanasia Amanda (Applied Science and Engineering Progress, 2024)
The development of novel materials based on renewable materials with beneficial properties that assist with energy efficiency and conservation has been encouraged by increasing consciousness of environmental issues. This research intends to use sustainable cellulose nanocrystals (CNC) obtained from oil palm empty fruit bunches (OPEFB) as reinforcement to enhance the properties of rigid polyurethane foam (RPUF). RPUF reinforcement with varied CNC concentrations (0.25–1 wt%) was examined by foaming behavior, surface morphology, mechanical properties, thermal insulation properties, dimensional stability, efficiency energy study, and CO2 reduction through their thermal conductivity values. The results achieved an optimal improvement of mechanical properties of the RPUF composite by around 23.53% compared to RPUF control, at the addition of 0.5 wt% of CNC concentration while maintaining the density of 37–39 kg/m3. Further, incorporating CNC improved thermal insulating performance by 9.95%, as reflected by decreased thermal conductivity from 0.0292 W/mK to 0.0269 W/mK and decreased cell size by 28.12%. Finally, based on the energy and cost efficiency studies, RPUF-CNC composites offer up to 0.78 kWh/m2 and 0.031 kWh/m2 compared to conventional wall materials made of concrete and wood, respectively. Furthermore, it contributed to reduced greenhouse gas (GHG) emissions by 110 and 7.2 kg CO2/year compared to concrete and wood, respectively. This work demonstrates the promising use of eco-friendly building insulation materials to mitigate the energy and environmental crisis.